Immune Destruction of Larval Taenia crassiceps in Mice - Mooney, K. A. (American Society for Microbiology, 2000)
Immune destruction of larval Taenia crassiceps was examined by first injecting BALB/cJ mice subcutaneously with larval buds and 30 to 60 days later challenging the mice with larvae injected into the peritoneal cavity. The larvae injected intraperitoneally (i.p.) secondarily are killed by host cells that completely encase the larvae in a thick sheath. The peritoneal exudate cells and the cytokines they produced were characterized by flow cytometry, enzyme-linked immunosorbent assays (ELISAs), and reverse transcription PCR (RT-PCR). No changes in percentage of CD4(+) T cells, CD8(+) T cells, B1 cells, or macrophages were detected in the peritoneal cavities of mice that were killing larvae compared to mice with a primary 7-day infection i.p. Both RT-PCR and ELISA demonstrated a decrease in cytokines including gamma interferon (IFN-γ), interleukin-4 (IL-4), and IL-10 in mice that were killing the larvae compared to control mice infected for 30 to 60 days i.p. alone, although there was little difference compared to mice infected for 7 days i.p. alone. Serum cytokine levels in mice that were killing the larvae showed a decrease in IFN-γ and IL-4, an increase in IL-10 when compared to mice infected for 30 to 60 days i.p. alone, and increases in all cytokines compared to mice infected for 7 days i.p. alone. Inhibition of nitric oxide production did not significantly affect the number or the viability of larvae in the peritoneal cavity of mice that were killing larvae during secondary infection.